Adaptive Nanoparticle-Polymer Complexes as Optical Elements: Design and Application in Nanophotonics and Nanomedicine; Laser and Photonics Reviews; Vol. 15, iss. 9 - Taljyanov P. Pavel; Fatkhutdinova Landysh Fatkhutdinova; Timin A. S. Aleksandr Sergeevich; Milichko V. A. Valentin; Zyuzin M. V. Mikhail (2021, 2021)
Title screen